Clinical and radiographic success of three adhesive restorative materials in primary molar proximal lesions: A randomized clinical trial - S K Inthihas; S V. S G. Nirmala; Venkata Ratnakumar Rudhravarm (Wolters Kluwer Medknow Publications, 2019)
Aim: The aim of this study was to evaluate and compare the clinical and radiographic success of primary molar proximal lesions in 4-8 years children restored with three adhesive restorative materials followed up for 12 months. Materials and Methods: This study was carried out on 102 primary molars of 51 children in the age range of 4-8 years. In all the participants, Class II lesions were restored and randomly allocated into three material groups as giomer group, nano-ionomer group, and light-cured glass-ionomer cement (LC-GIC) group based on the restorative material used. All the restorations were evaluated and scored according to federation dentaire internationale (FDI) criteria for clinical and radiographic success rate at 3, 6, and 12 months' interval. Data were formulated in a predesigned format and were subjected to statistical analysis using the Chi-square test and Fisher's exact test. Results: There was no statistically significant difference observed among the restorative material groups to all the properties of FDI criteria. The overall success rates of restorative materials at 3, 6, and 12 months' interval were as follows: giomer - 100%, 100%, and 94.1%; nano-ionomer - 97%, 94%, and 85.3%; and LC-GIC - 100%, 94%, and 88.2%. Conclusion: The highest clinical success rate was found for the giomer group followed by LC-GIC group and the least for the nano-ionomer group, whereas the highest radiographic success rate was found for giomer as well as LC-GIC group and the least for nano-ionomer group.